Establishment and verification of reference intervals for blood cell analysis in extremely high altitude - Yuan, Zhimin; Zhuang, Jian (Frontiers in Physiology, 2024)
Objective This study aimed to establish the reference intervals for complete blood count (CBC) in healthy adults at very high altitudes. Methods This study recruited 4,863 healthy adults (3,598 males and 1,265 females) who received routine health check-ups at Ali District People’s Hospital from January 2019 to December 2021 through the LIS system. CBC was detected by the XT-4000i automatic cell analyzer and statistically analyzed by SPSS 23.0 software (between-groups comparison, diagnostic concordance comparison). In addition, 20 health check samples were collected in 2022 to validate the established reference intervals. Results The CBC count showed a non-normal distribution in each item separately. The white blood cell (WBC), neutrophil (NEUT), lymphocyte (LYMPH), monocyte (MONO), eosinophil (EO), basophil (BASO), red blood cell (RBC), hemoglobin (HGB), hematocrit (HCT), mean corpuscular volume (MCV), mean hemoglobin content (MCH), and mean erythrocyte hemoglobin concentration (MCHC) levels of healthy adults were significantly different from the national clinical reference range (p < 0.05). There were significant differences between males and females in RBC, HGB, and HCT levels (p < 0.05). The new reference intervals were less consistent with the expert consensus CBC reference intervals (p < 0.05). Compared with the other reference intervals, the diagnostic value of the reference screening interval established was significantly higher in this study (p < 0.05). The reference range established is verified by 20 independent samples from 2022, and the results are acceptable. Conclusion This study preliminarily established reference intervals for complete blood counts of healthy adults at high altitudes in the Ali region of Tibet to provide a reference point for understanding routine blood markers in permanent residents of high-altitude environments and illustrate the need for regular establishment of laboratory reference intervals on a regular basis.